2016
DOI: 10.1002/anie.201609437
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Frequency CH Stretch Vibrations of Free Alkoxide Ions

Abstract: CH stretches in hydrocarbon cations often shift to lower frequencies relative to neutral molecules, because they do not have sufficient electrons to give every bond an electron pair. A parallel effect in negatively charged species has not been previously observed. Here we show that CH bond weakening occurs in alkoxide anions as a consequence of hyperconjugation. The reasoning differs somewhat from the case of positively charged ions, but the net effect is the same: to lower CH stretching frequencies by hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…It's revealed experimentally by Morton et al that the C–H bond of alkoxide species could be weakened and lead to aldehyde group formation based on the lower CH stretching frequencies relative to the neutral alkanol molecule by using IR multiple photon dissociation (IRMPD) spectra. 38 In this work, the low energy barrier for the Al–COH 2 + formation from Al–OCH 3 (Al methoxide) through TS2 is in good agreement with this experimental result. Additionally, Lercher et al also demonstrated that the LAS sites could promote the yield of HCHO in ZSM-5 zeolite by hydride transfer.…”
Section: Results and Disscusionsupporting
confidence: 88%
“…It's revealed experimentally by Morton et al that the C–H bond of alkoxide species could be weakened and lead to aldehyde group formation based on the lower CH stretching frequencies relative to the neutral alkanol molecule by using IR multiple photon dissociation (IRMPD) spectra. 38 In this work, the low energy barrier for the Al–COH 2 + formation from Al–OCH 3 (Al methoxide) through TS2 is in good agreement with this experimental result. Additionally, Lercher et al also demonstrated that the LAS sites could promote the yield of HCHO in ZSM-5 zeolite by hydride transfer.…”
Section: Results and Disscusionsupporting
confidence: 88%
“…These theoretical results were confirmed by the IRMPD spectra of several isopropoxy anions . Oomens et al.…”
Section: Small Moleculesmentioning
confidence: 56%
“…These theoretical results were confirmed by the IRMPD spectra of severali sopropoxy anions. [12] Oomens et als howed that the C(2)ÀHs tretching of isopropoxya nions is found at frequencies well below those of aldehyde CÀHb onds ( Figure 2). The aldehyde CÀHb ond vibrations are the lowest lying CÀH vibrations found in common organic compounds.T hey confirmed the positiono ft he C(2)ÀHs tretching band in the 2200-2400 cm À1 range by deuterium labelling experiments,t hus suggesting that charging molecules both negatively and positively weakens the affected bonds.…”
Section: What Is the Effect Of Charge?mentioning
confidence: 96%
See 1 more Smart Citation
“…The use of benchtop systems complements IRMPD measurements performed using free-electron lasers (FELs) that deliver infrared radiation usually within the range 600-2000 cm −1 with enough power to induce dissociation of selected trapped ions, 40 although higher harmonics can be used to extend the operational range of FELs. 64 However, these systems rely on linear electron accelerators to produce a relativistic beam to be injected into an undulator, and therefore are still very expensive and not easily implemented. 65 For this reason, there are effectively only three open FEL-IRMPD facilities in the world: CLIO in France, 66 FELIX in The Netherlands 67 and the FHI-FEL in Germany.…”
Section: Introductionmentioning
confidence: 99%